2017
DOI: 10.1038/s41598-017-02111-6
|View full text |Cite|
|
Sign up to set email alerts
|

Levels of Faecal Calprotectin and Magnetic Resonance Enterocolonography Correlate with Severity of Small Bowel Crohn’s Disease: A Retrospective Cohort Study

Abstract: Few studies have evaluated the usefulness of fecal calprotectin (FC) or magnetic resonance enterography (MRE) in diagnosing active Crohn’s disease (CD) of the small bowel. In the study, we investigated the reliability of FC and MRE in assessing the activity of ileal CD and further explored the relationship between levels of FC and MRE scores. A total of 221 patients were diagnosed with ileal or ileo-colitis CD in our department between July 2012 and October 2016. The global magnetic resonance index of activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
5
21
0
1
Order By: Relevance
“…Multiple investigators have explored the range of FCP levels which most accurately reflects mucosal inflammation that range from 50 to 250 ug/mL [7][8][9][10][11][12]. While several prior studies have used FCP levels below 250 ug/mL [7][8][9][10][11], we confirmed that the FCP cutoff value of 250 ug/mL significantly correlated with the presence of active disease and severity of inflammation confirmed by both MRE and colonoscopy, respectively. This FCP cutoff value, which is in line with the Colombel et al…”
Section: Correlation Between Cdeis and Mariasupporting
confidence: 68%
See 3 more Smart Citations
“…Multiple investigators have explored the range of FCP levels which most accurately reflects mucosal inflammation that range from 50 to 250 ug/mL [7][8][9][10][11][12]. While several prior studies have used FCP levels below 250 ug/mL [7][8][9][10][11], we confirmed that the FCP cutoff value of 250 ug/mL significantly correlated with the presence of active disease and severity of inflammation confirmed by both MRE and colonoscopy, respectively. This FCP cutoff value, which is in line with the Colombel et al…”
Section: Correlation Between Cdeis and Mariasupporting
confidence: 68%
“…The median CDEIS was 22 with a range of 6 to 38; median MaRIA was 22.5 with a range of 5 to 30. FCP, MRE, and Crohn's Disease activity but in the small bowel, not the colon, as in this study [10][11][12].…”
Section: Correlation Between Cdeis and Mariamentioning
confidence: 84%
See 2 more Smart Citations
“…Moy and colleagues 59 reassured previous results, however, their study differ in design and goals and did not assess MRE response to therapy but rather the ability to detect mucosal healing. Ye and colleagues 44 determined a cutoff value of 6.8 for detection of mucosal healing [area under the curve (AUC) 0.881, sensitivity 100%, specificity 79.2%] however they used a different value of SES-CD for mucosal healing as a standard reference.…”
Section: Clinical Implications Of Mre Indicesmentioning
confidence: 99%